Sale of fresh forage: a new cash crop for smallholder farmers in Yasothon, Thailand - Nakamanee, G; Srisomporn, W; Phengsavanh, P; Samson, J; Stür, Werner W. (2008)
This paper describes the emergence of a new cash-crop enterprise the sale of fresh forage for smallholder farmers in Yasothon, northeast Thailand. In 1999, a group of 13 farmers started to produce forages for sale to beef cattle producers and traders. By 2006, this had grown to the extent that more than 600 farmers were growing and selling fresh forage. A study was carried out to describe the forage-for-sale production system and to evaluate its profitability and sustainability. Methods used included farmer group discussions, semi-structured interviews with individual farmers, weighing of forage samples and soil and plant analyses. The main forage species grown for sale was Panicum maximum cv. Simuang (purple guinea grass), a high-yielding, upright, leafy grass. Production was very intensive with plants grown at a spacing of 50 × 50 cm, with high rates of both organic and inorganic fertilisers and some irrigation. Average forage yields were 33 t DM/ha/yr in the establishment year and 46 t DM/ha/yr in subsequent years. Mean protein concentration (DM basis) in forage offered for sale was 10% in the wet season and 14% in the dry season. Net returns were very high (US$2500 3800/ha/yr), which far exceeded the gross return of US$590/ha/yr from rice production. Farmers replanted guinea grass after 2 3 years. Prices for fresh forage were highest in the late dry season (US$0.042/kg), when prices were almost twice those during the peak of the wet season (US$0.025/kg). Only farmers with access to irrigation could supply during this time and, by 2006, the production of forage for sale had shifted towards irrigated areas. An issue of concern is the imbalance between nutrient off-take by removal of cut forage and current fertiliser applications, which are urea and chicken manure. Chicken manure has an N:P:K nutrient ratio of 1:1:0.7. The use of these fertilisers results in an oversupply of 200 400 kg/ha of phosphorus per year and a large deficit of potassium. One possible solution would be to substitute cattle manure, with a more suitable N:P:K ratio of 1:0.3:0.8, for chicken manure. Cattle manure is available locally and used on-farm by farmers raising cattle but is not traded extensively. Another option would be to make use of single-nutrient fertilisers to better balance fertiliser applications and nutrient off-take. Unfortunately, these are not readily available in north-east Thailand. The sale of fresh forage has emerged as a new farm enterprise, providing high returns for smallholder farmers with access to markets and irrigation facilities. The system must be fine tuned by balancing nutrient supply more closely with nutrient off-take to ensure the long-term sustainability of the venture.